Repression, Exile, and Democracy : Uruguayan Culture - Popkin, Louise B.; Popkin, Louise B.; Sosnowski, Saúl (Book collections on Project MUSE., 1993)
"Most of the essays in this book were originally presented at a 1986 conference on Uruguay; however, several of the chapters were updated immediately prior to publication. Overall, work serves as excellent document on prevailing cultural perspectives in initial years of the return to democracy. Several articles provide a stimulating perspective on dictatorship and democracy"--Handbook of Latin American Studies, v. 57.